2018
DOI: 10.31842/jurnal-inobis.v2i1.63
|View full text |Cite
|
Sign up to set email alerts
|

The effect of firm created content and user generated content evaluation on customer-based brand equity

Abstract: The purpose of this paper is to investigate social media communication and its impact on customer-based brand equity. Compare two social media communication tools that are firm created content and user generated content. A total of 114 data sets developed through a standard online survey to investigate the impact of firm created content and user-generated content evaluation in social media on brand awareness / association, perceived quality and brand loyalty to the cosmetics industry in Indonesia. A mini surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This study identified that social brand engagement plays an important mediating role in driving brand equity of the HEIs, answering the call for empirical research into the drivers and outcomes of brand equity (Šerić et al ., 2018). The previous study only confirms the direct impact of UGC, FGC and brand equity (Hermaren and Achyar, 2018), and we confirmed that it should go through social brand engagement in creating brand equity. The findings provide compelling evidence that social brand engagement mediates the relationship between UGC, FGC and brand equity, which had not received much attention in the literature.…”
Section: Discussionsupporting
confidence: 73%
“…This study identified that social brand engagement plays an important mediating role in driving brand equity of the HEIs, answering the call for empirical research into the drivers and outcomes of brand equity (Šerić et al ., 2018). The previous study only confirms the direct impact of UGC, FGC and brand equity (Hermaren and Achyar, 2018), and we confirmed that it should go through social brand engagement in creating brand equity. The findings provide compelling evidence that social brand engagement mediates the relationship between UGC, FGC and brand equity, which had not received much attention in the literature.…”
Section: Discussionsupporting
confidence: 73%
“…There is a notorious gap in this correlation in the tourism sector. Hermaren and Achyar (2018) found no significant connection between brand loyalty and user-generated content in the cosmetics sector. This contradicts the conclusions drawn by Schivinski and Dabrowski (2015), who identified a significant correlation between user-created content and brand loyalty.…”
Section: Discussionmentioning
confidence: 77%